2012
DOI: 10.3343/alm.2012.32.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Modified Multiple-locus Variable-number Tandem-repeat Fingerprinting with Pulsed-field Gel Electrophoresis for Typing Clinical Isolates of Staphylococcus aureus

Abstract: BackgroundMultiple-locus variable-number tandem-repeat fingerprinting (MLVF) is based on multiplex PCR, utilizing variable number tandem repeat. Our goal was to compare the performance of MLVF in distinguishing clinical Staphylococcus aureus isolates with that of pulsed-field gel electrophoresis (PFGE), which has traditionally been the gold standard.MethodsSixty-three clinically significant S. aureus isolates were tested using both PFGE and MLVF. Multiplex PCR for MLVF was performed using PCR primers for clfA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Nonetheless, other authors identified differences in resistance profiles, including multidrug‐resistant strains (Bakhshi and others ). The presence of 6 genotypes indistinguishable from human clinical isolates suggests that the survival data generated by this study are applicable to zoonotic Campylobacter strains (Chung and others ). In addition, because of the potential to identify and determine groups of bacteria or food outbreaks, this methodology can be applied for assessing gene location, such as gentamicin‐resistant genes on a plasmid or the chromosome (Yao and others ).…”
Section: Molecular Tools Used For Typing Campylobacter Spp In Foods mentioning
confidence: 76%
See 1 more Smart Citation
“…Nonetheless, other authors identified differences in resistance profiles, including multidrug‐resistant strains (Bakhshi and others ). The presence of 6 genotypes indistinguishable from human clinical isolates suggests that the survival data generated by this study are applicable to zoonotic Campylobacter strains (Chung and others ). In addition, because of the potential to identify and determine groups of bacteria or food outbreaks, this methodology can be applied for assessing gene location, such as gentamicin‐resistant genes on a plasmid or the chromosome (Yao and others ).…”
Section: Molecular Tools Used For Typing Campylobacter Spp In Foods mentioning
confidence: 76%
“…This methodology is widely used for typing to obtain a clear comparison of genomic relationships among bacterial isolates, with the ability to correlate isolated microorganisms from different sites and samples. This technique is classified as a 3rd‐generation technique that uses molecular interaction and is considered the “gold standard” for evaluating interrelationships between isolates, including foodborne pathogens (Goering ; Chung and others ; Noormohamed and Fakhr ). Additionally, a network project, called Campynet, to standardize subtyping methods for Campylobacter in the European Union was created in 1998.…”
Section: Molecular Tools Used For Typing Campylobacter Spp In Foods mentioning
confidence: 99%
“…Isolates that are genetically distant present differences in their profile of bands and those that are identical share the same pattern of bands. 3,10 The objective of this pilot study was to describe the frequency of S. aureus carriage in hemodialyzed patients attending the nephrology department of the Hospital de Clínicas, and perform the clustering analysis of isolates by the MLVA molecular technique.…”
Section: Introductionmentioning
confidence: 99%
“…To compare data obtained from different runs or-even worse-from different laboratories, strict protocols must be applied (Swaminathan et al, 2001). Owing to its high discriminatory power, PFGE is the method of choice in outbreak investigation, although faster and simpler methods are highly appreciated (Ruppitsch et al, 2007a(Ruppitsch et al, , 2007cFretz et al, 2010aFretz et al, , 2010bHuhulescu et al, 2011;Chung et al, 2012). In our laboratory, PFGE analysis was applied for epidemiological investigation and elucidation of a multinational listeriosis outbreak in Austria, Germany, and the Czech Republic in the years 2009-2010 (Fretz et al, 2010a(Fretz et al, , 2010b and an ongoing outbreak in Germany (Ruppitsch et al, 2015b).…”
Section: Pulsed-field Gel Electrophoresis (Pfge)mentioning
confidence: 99%